2016
DOI: 10.1002/anie.201608615
|View full text |Cite
|
Sign up to set email alerts
|

Bi−P Bond Homolysis as a Route to Reduced Bismuth Compounds and Reversible Activation of P4

Abstract: Bismuth diphenylphosphanides Bi(NON )(PPh ) (NON =[O(SiMe NR) ], R=tBu, 2,6-iPr C H , Aryl) undergo facile decomposition via single-electron processes to form reduced Bi and P species. The corresponding derivatives Bi(NON )(PCy ) are stable. Reaction of the isolated Bi radical Bi(NON ) with white phosphorus (P ) proceeds with the reversible and selective activation of a single P-P bond to afford the bimetallic μ,η -bicyclo[1.1.0]tetraphosphabutane compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
65
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 43 publications
(32 reference statements)
8
65
0
4
Order By: Relevance
“…[15] Related to IVC,g allium(I) metal centres have been used to access stable distibenes [VII] 2 , [16] and the bulky amide ligand pioneered by Jones has also been used in this context ([VIII] 2 ). [17] We have previously reported the synthesis andr eactivityo f low valent main group (Al, In, Sb, Bi)c omplexes supported by bis(amidodimethyl)disiloxane ligands [O(SiMe 2 NR) 2 ] 2À ([NON R ] 2À , R = tBu, [18] 2,6-diisopropylphenyl = Dipp, [18,19] 2,6-dimethylphenyl = Dmp, [18c, 19e] and 2,6-bis(benzhydryl)-4-tBu-phenyl = tBu-Bhp [18d] ). In group 15 chemistry,w eh ave shown that reduction of the bismuth(III) chloride Bi(NON R )Cl using magnesium or LiHBEt 3 generates either the corresponding bismuth(II) radical [Bi(NON R )]C (R = Dipp or tBu-Bhp), [18d, 19a] or dibismuthane [Bi(NON R )] 2 (R = tBu).…”
Section: Introductionmentioning
confidence: 99%
“…[15] Related to IVC,g allium(I) metal centres have been used to access stable distibenes [VII] 2 , [16] and the bulky amide ligand pioneered by Jones has also been used in this context ([VIII] 2 ). [17] We have previously reported the synthesis andr eactivityo f low valent main group (Al, In, Sb, Bi)c omplexes supported by bis(amidodimethyl)disiloxane ligands [O(SiMe 2 NR) 2 ] 2À ([NON R ] 2À , R = tBu, [18] 2,6-diisopropylphenyl = Dipp, [18,19] 2,6-dimethylphenyl = Dmp, [18c, 19e] and 2,6-bis(benzhydryl)-4-tBu-phenyl = tBu-Bhp [18d] ). In group 15 chemistry,w eh ave shown that reduction of the bismuth(III) chloride Bi(NON R )Cl using magnesium or LiHBEt 3 generates either the corresponding bismuth(II) radical [Bi(NON R )]C (R = Dipp or tBu-Bhp), [18d, 19a] or dibismuthane [Bi(NON R )] 2 (R = tBu).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] To date,the only catalytic application of an isolable bismuth radical is the dehydrogenative coupling of SiPhH 3 with TEMPO to give SiPhH 2 (TEMPO) (TEMPO = tetramethylpiperidinyl-N-oxide). [12,13] While of great fundamental significance,t he bismuth radical showed al ow cata-lytic activity (75 %conversion after 15 d) [14] and the use of the isolable radical TEMPO as as ubstrate was necessary to facilitate the reaction.…”
mentioning
confidence: 99%
“…Finally,t he transition metal bismuthanes 2-4 were tested as catalysts in the cyclo-isomerization of S1. Whereas the cobalt species 2 showed low activity,t he iron compound 3 and the manganese compound 4 led to yields of 24 %a nd 73 %, respectively (entries [12][13][14]. Focusing on manganese bismuthanes as the most active species,t he synthesis of literature-known [15a] [BiPh 2 (Mn(CO) 5 )] (7)w as improved (see Supporting Information).…”
mentioning
confidence: 99%
“…Later, it became clear that 8 can also be prepared by treatment of [O{Si(Me) 2 N(Dip)} 2 ]BiCl with LiHBEt 3 or LiPPh 2 . Upon Bi–H or Bi–P homolysis, 8 and half an equivalent of H 2 or [Ph 2 P] 2 were generated, respectively (Scheme ) . The influence of the steric demand of the diamidodisiloxane ligand was examined by employing a sterically less demanding ( t Bu) and a more demanding (Ar' = 2,6‐Ph 2 HC‐4‐ t BuC 6 H 2 ) N‐substituent, yielding dibismuthane {[O{Si(Me) 2 N( t Bu)} 2 ]Bi} 2 ( 9 ) and the second isolable bismuthanyl radical [O{Si(Me) 2 N(Ar')} 2 ]Bi · ( 10 ), respectively (Scheme ).…”
Section: Neutral Two‐coordinate Pnictanyl Radicalsmentioning
confidence: 99%
“…Remarkably, dibismuthane 9 shows radical‐like behavior, even though no evidence for the dissociation of 9 into monomers was observed. Radical 8 was found to reversibly cleave one P–P edge of the P 4 tetrahedron, resulting in Bi‐stabilized tetraphosphabicyclo[1.1.0]butane 11 , whereas reactions of 8–10 with S 8 yield complexes of the type [O{Si(Me) 2 N(R)} 2 ]Bi} 2 ( µ ‐S n ) (R = t Bu, n = 1, 3; R = Dip, n = 1, 3, 5) and {[O{Si(Me) 2 N(Ar')} 2 ]Bi(S 4 )} 2 ( 12 ), respectively (Scheme ) . According to the solid‐state structure and DFT calculations of 12 , two [O{Si(Me) 2 N(Ar')} 2 ]Bi(S 4 ) · radical units are linked by π *– π * interactions between the terminal sulfur atoms of the S 4 moieties .…”
Section: Neutral Two‐coordinate Pnictanyl Radicalsmentioning
confidence: 99%